'Verdammt Metall': Marx's use of Shakespeare in his Critique of Exchange-value. Issue 1 (3rd April 2017) - Smith, Christian A.
Abstract : Karl Marx quoted from and alluded to Shakespeare's plays in his critique of capitalism. Lines and imagery from Shakespeare, and other world literary authors including Cervantes and Ovid, were useful for Marx as he logically derived the categories that make up the dialectical materialist critique of capitalism. Shakespeare's plays stake a place in the historical development of the dialectic, from its Classical form—a voluntary method of philosophical exploration—into its Hegelian form—the force by which meaning expresses itself through history. This Shakespearean contribution to the development of the dialectic serves as a common ground, a shared formal substrate, a condition of possibility through which the influence could occur. A feature of the ground is that, as a field of shared concerns and similar methodology, it facilitates the authority of Shakespeare's texts to act as an influence on Marx's texts. This influence is particularly visible in the manner in which Marx used the plays to write about exchange-value, its inversions and contradictions. Marx's use of Shakespeare in his logic of exchange-value and the contradictions it generates is the topic of this essay. Abstract :